PENGARUH CELEBRITY ENDORSER DAN KUALITAS PRODUK TERHADAP BRAND IMAGE DAN KEPUTUSAN PEMBELIAN MOBIL MITSUBISHI XPANDER DI KOTA PEKANBARU - Luhut Jerrywanto; Restuti Sri; Noviasari Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The development of technology and increasing public knowledge and everchanging consumer tastes cause business competition to be increase ngly tight. One business that is experiencing very stiff competition today is the automotive sector. Automotive manufacturers must apply the right marketing strategies and maintain the quality of products in the car products that will be produced in order to be able to maintain their market share. In Indonesia, Low Multi Purpose Vehicel (LMPV) cars are in high demand by the public because this type of car is designed to be a family car and has a fairly affordable price. Car products contained in the type of Low Multi Purpose Vehicel (LMPV) are Avanza, Xpander, Xenia, Ertiga, and Mobilio. In this study the object chosen for research was a Mitsubishi Xpander car. This research aims to find out the influence of Celebrity Endorser and Product Quality on Brand Image and Purchasing Decisions for Mitsubishi Xpander cars in Pekanbaru City. This research uses a quantitative approach. The sample in this study was 130 people who were owners of Mitsubishi Xpander cars and had a minimum age of 30 years. Sampling uses non-probability sampling methods and purposive sampling techniques. This research instrument uses questionnaires and is analyzed using path analysis with the help of SPSS software version 21. The results of this study showed that the variables celebrity endorser and product quality have a positive and significant effect on brand image. Celebrity Endorser and Product Quality variables have a positive and significant effect on Purchasing Decisions both directly and through Brand Image, as well as Brand Image variables have a positive and significant effect on Purchasing Decisions.Keywords : Celebrity Endorser, Product Quality, Brand Image, Purchasing Decisions, Path Analysis